Loading [MathJax]/jax/element/mml/optable/BasicLatin.js
Skip to main content

Section 10.4 Examples

Subsection 10.4.1 The 2Γ—2 case

Let's compute the adjoint of the general 2Γ—2 matrix A=[abcd]. First, the minors.

Minor determinants for \(2 \times 2\) matrices

In the matrix of cofactors for a 2Γ—2 matrix, the off-diagonal cofactors become negative, and then the adjoint is the transpose of that.

CA=[dβˆ’cβˆ’ba]adjA=[dβˆ’bβˆ’ca]

The inverse of A is then the reciprocal of the determinant times the adjoint, so that

Aβˆ’1=1adβˆ’bc[dβˆ’bβˆ’ca],

as promised in Proposition 5.5.4.

Subsection 10.4.2 Computing an inverse using the adjoint

As mentioned, using the adjoint to compute the inverse of a matrix is not very efficient for matrices larger than 2Γ—2. In most cases, you are better off using the row reduction method. However, there are situations where you might want to use the adjoint instead, as in the example below.

Example 10.4.1. Using the adjoint to compute an inverse.

It can be tedious to row reduce a matrix with variable entries. Consider

X=[x1βˆ’1xβˆ’10x0x1].

To row reduce X, our first step would be to obtain a leading one in the first column. We might choose to perform R1β†’1xR1, except that this operation would be invalid in the case that x=0. Or we might choose to perform R2β†’1xβˆ’1R2, except that this operation would be invalid in the case that x=1. So to row reduce X we would need to consider three different cases, x=0, x=1, and xβ‰ 0,1, performing different row reduction sequences in each of these cases. And when we get to the point of trying to obtain a leading one in the second column, we might discover there are even more cases to consider.

So instead we will attempt to compute the inverse of X using the adjoint. First, the minors.

M11=|0xx1|=βˆ’x2M12=|xβˆ’1x01|=xβˆ’1M13=|xβˆ’100x|=x2βˆ’xM21=|1βˆ’1x1|=1+xM22=|xβˆ’101|=xM23=|x10x|=x2M31=|1βˆ’10x|=xM32=|xβˆ’1xβˆ’1x|=x2+xβˆ’1M33=|x1xβˆ’10|=1βˆ’x

We obtain the matrix of cofactors by making certain minor determinants negative, according to the 3Γ—3 pattern of cofactor signs, and then the adjoint is the transpose.

CX=[βˆ’x21βˆ’xx2βˆ’xβˆ’1βˆ’xxβˆ’x2xβˆ’x2βˆ’x+11βˆ’x]adjX=[βˆ’x2βˆ’1βˆ’xx1βˆ’xxβˆ’x2βˆ’x+1x2βˆ’xβˆ’x21βˆ’x]

To compute the inverse of X, we still need its determinant. But we already have all the cofactors, so a cofactor expansion will be easy. Let's do a cofactor expansion of det along the third row. (Remember that the cofactors already have the appropriate signs, so we are just summing β€œentry times cofactor” terms.)

\begin{equation*} \det X = 0x + x(-x^2-x+1) + 1(1-x) = 1 - x^3 - x^2 \end{equation*}

Finally, we obtain a formula for the inverse of X that is valid for every value of x for which the determinant is nonzero,

\begin{equation*} \inv{X} = \frac{1}{1 - x^3 - x^2} \begin{bmatrix} -x^2 \amp -1-x \amp x \\ 1-x \amp x \amp -x^2-x+1 \\ x^2-x \amp -x^2 \amp 1-x \end{bmatrix}. \end{equation*}

Subsection 10.4.3 Cramer's rule

Example 10.4.2. Using Cramer's rule to compute individual variable values in a system of equations.

Consider the system

\begin{equation*} \left\{\begin{array}{rcrcrcrcr} x_1 \amp - \amp x_2 \amp + \amp 2x_3 \amp + \amp x_4 \amp = \amp 1,\\ 2x_1 \amp \amp \amp + \amp x_3 \amp + \amp x_4 \amp = \amp 1,\\ \amp \amp x_2 \amp \amp \amp - \amp 3x_4 \amp = \amp 0,\\ x_1 \amp - \amp 2x_2 \amp - \amp x_3 \amp \amp \amp = \amp 1,\\ \end{array}\right. \end{equation*}

with coefficient matrix and vector of constants,

\begin{align*} A \amp= \left[\begin{array}{rrrr} 1 \amp -1 \amp 2 \amp 1 \\ 2 \amp 0 \amp 1 \amp 1 \\ 0 \amp 1 \amp 0 \amp -3 \\ 1 \amp -2 \amp -1 \amp 0 \end{array}\right], \amp \uvec{b} \amp = \begin{bmatrix} 1 \\ 1 \\ 0 \\ 1 \end{bmatrix}. \end{align*}

Conveniently, we have already computed \det A = -27 in Example 8.4.5 (and again in Example 9.3.1). Since \det A \neq 0\text{,} we know that A is invertible and so the system has one unique solution. Suppose we want to know the value of x_2 in the solution. We can form the matrix A_2\text{,} where the second column of A is replaced by \uvec{b}\text{,}

\begin{equation*} A_2 = \left[\begin{array}{rrrr} 1 \amp 1 \amp 2 \amp 1 \\ 2 \amp 1 \amp 1 \amp 1 \\ 0 \amp 0 \amp 0 \amp -3 \\ 1 \amp 1 \amp -1 \amp 0 \end{array}\right]\text{,} \end{equation*}

and compute \det A_2 by a cofactor expansion along the third row (expanding the corresponding 3\times 3 minor determinant along the first row),

\begin{align*} \det A_2 \amp = -(-3)\left\lvert\begin{array}{rrr} 1 \amp 1 \amp 2 \\ 2 \amp 1 \amp 1 \\ 1 \amp 1 \amp -1 \end{array}\right\rvert\\ \amp = 3\left( 1 \left\lvert\begin{array}{rr} 1 \amp 1 \\ 1 \amp -1 \end{array}\right\rvert - 1 \left\lvert\begin{array}{rr} 2 \amp 1 \\ 1 \amp -1 \end{array}\right\rvert + 2 \left\lvert\begin{array}{rr} 2 \amp 1 \\ 1 \amp 1 \end{array}\right\rvert \right)\\ \amp = 3\bbrac{(-1-1)-(-2-1)+2(2-1)}\\ \amp = 9\text{.} \end{align*}

Thus, the value of x_2 in the one unique solution to the system is

\begin{equation*} x_2 = \frac{\det A_2}{\det A} = \frac{9}{-27} = -\frac{1}{3} \text{.} \end{equation*}

If we also want to know the value of x_4\text{,} we form the matrix A_4\text{,} where the fourth column of A is replaced by \uvec{b}\text{,}

\begin{equation*} A_4 = \left[\begin{array}{rrrr} 1 \amp -1 \amp 2 \amp 1 \\ 2 \amp 0 \amp 1 \amp 1 \\ 0 \amp 1 \amp 0 \amp 0 \\ 1 \amp -2 \amp -1 \amp 1 \end{array}\right], \end{equation*}

and compute \det A_4 (again by a cofactor expansion along the third row, followed by an expansion along the first row of the corresponding 3\times 3 minor determinant),

\begin{align*} \det A_4 \amp = -1 \left[\begin{array}{rrr} 1 \amp 2 \amp 1 \\ 2 \amp 1 \amp 1 \\ 1 \amp -1 \amp 1 \end{array}\right]\\ \amp = -1\left( 1 \left[\begin{array}{rr} 1 \amp 1 \\ -1 \amp 1 \end{array}\right] - 2 \left[\begin{array}{rr} 2 \amp 1 \\ 1 \amp 1 \end{array}\right] + 1 \left[\begin{array}{rr} 2 \amp 1 \\ 1 \amp -1 \end{array}\right] \right)\\ \amp = -\bbrac{(1+1) - 2(2-1) + (-2-1)}\\ \amp = 3. \end{align*}

Thus, the value of x_4 in the one unique solution to the system is

\begin{equation*} x_4 = \frac{\det A_4}{\det A} = \frac{3}{-27} = -\frac{1}{9} \text{.} \end{equation*}